Pengaruh Model Pembelajaran Problem Based Learning Terhadap Motivasi Dan Hasil Belajar Siswa Kelas V SD Pada Materi Ekosistem - Ria Safitri; Sopiyan Hadi; Widiasih Widiasih (Jurnal Penelitian Pendidikan IPA, 2023)
The background of this study is the low learning motivation and learning outcomes of grade V students of SDN 01 Banjar Sari. This study aims to determine the effect of the Problem Based Learning (PBL) Model on student learning motivation and learning outcomes of grade V students at SDN 01 Banjar Sari. This research uses a type of experimental research type of Quasi-Experimental research design. The method used is by quantitative research methods, with. The quasi-experimental design used in this study was a pretest posttest nonequivalent control group design. This study used two classes consisting of a control class and an experimental class. In the experimental class, they will get a Problem Based Learning model, while in the control class they will get an expository learning model. The population of this study is all grade V students of SDN 01 Banjar Sari for the 2021/2022 academic year. The number of population subjects is 60 students divided into 2 classes, namely VA and VB classes, with each VA class 30 students and VB 30 students. Data collection in this study used Nonprobability sampling technique. The results of this study show that the Problem Based Learning model affects student learning motivation by 100.00, the Problem Based Learning model affects student learning outcomes by 95.00. The average score of the learning outcomes of the control class was 57.00, the average score of the experimental class was 82.83. The average value of the control class learning motivation was 85.93 and the average value of experimental class learning motivation was 90.15.